CORRELATION OF SERUM HIGH-DENSITY LIPOPROTEIN CHOLESTEROL AND HOMOCYSTEINE LEVEL IN PATIENT WITH ACUTE MYOCARDIAL INFARCTION - Yayie Dwina Putri; Tuty Prihandani; Lillah Lillah; Rismawati Yaswir (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Acute Myocardial Infarction (AMI), one of the primary manifestation of coronary heart disease, is a significat cause of death worldwide. Hyperhomocysteinemia, a risk factor for cardiovascular disease, is caused by nutritional or genetic disturbances in homocysteine metabolism. The role of hyperhomocysteinemia in altered lipid metabolism presumed holds the key to an increased risk of cardiovascular disease. Hyperhomocysteinemia causes the reduction of serum High-Density Lipoprotein (HDL) cholesterol level by inhibiting hepatic synthesis of apo-A1 (significant apolipoprotein HDL). The aim of this study was to know the correlation between hyperhomocysteinemia and decreased HDL cholesterol levels for the management of cardiovascular disease risk factors. This research was an analytical study with cross-sectional design in 40 patients AMI who meet the inclusion and exclusion criteria and conduct blood test at the Central Laboratory of Hospital Dr. M. Djamil Padang and Biomedical Laboratory Faculty of Medicine Andalas University. The study was conducted in May 2016-Agustus 2017. Homocysteine level was measured by ELISA method. High-Density Lipoprotein level was performed by enzymatic colorimetric method. Data were analyzed by Spearman's correlation test. Research subjects were 40 people with male gender 30 (75%) and female 10 (25%), mean age 61.08 (11.09) year. The mean level of HDL cholesterol in patients with AMI is 41.93 ± 13.12 mg/dL. The mean level of homocysteine in patients with AMI is 25.36 ± 22.2 µmol/L. Spearman's correlation test showed a strong correlation between the levels of homocysteine and HDL cholesterol with r=-0.603 and p<0.01.